1990
DOI: 10.1007/bf02540752
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the total unsaturation in oils and margarines by fourier transform raman spectroscopy

Abstract: An improved Raman spectroscopic procedure for the determination of the total unsaturation in oils and fats using Fourier Transform Raman {FT-Raman} spectroscopy is described. An important advantage of FT-Raman for these samples is that the spectra are fluorescence-free unlike dispersive Raman which often uses visible excitation. Samples can be analyzed without any pre-treatment thus eliminating the need for dissolution in toxic solvents. The short acquisition time of FT-Raman and the ease of application allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 14 publications
3
82
1
Order By: Relevance
“…Quantification of the total degree of unsaturation is based on the integrated intensity or area of CDC stretching band near 1660 cm 1 , expressed as a ratio to the area of the CDO stretching band near 1750 cm 1 or the CH 2 scissoring band near 1445 cm 1 . 148,150 PCA applied to the Raman shifts of 138 edible oil and fat samples from 21 different sources, correlated with certain structural assignments or with the fatty acid content quantified by gas chromatography, showed clear classification of the samples according to their degree of unsaturation on the basis of a few wavenumbers. 152 It was concluded that the FT-Raman spectra provided information on the degree of unsaturation as well as the relative proportions of SFA, MUFA and PUFA, with the intensities near 3013, 1663 and 1264 cm 1 in particular showing high correlation with the fatty acid profiles determined by gas chromatography.…”
Section: Fatmentioning
confidence: 99%
“…Quantification of the total degree of unsaturation is based on the integrated intensity or area of CDC stretching band near 1660 cm 1 , expressed as a ratio to the area of the CDO stretching band near 1750 cm 1 or the CH 2 scissoring band near 1445 cm 1 . 148,150 PCA applied to the Raman shifts of 138 edible oil and fat samples from 21 different sources, correlated with certain structural assignments or with the fatty acid content quantified by gas chromatography, showed clear classification of the samples according to their degree of unsaturation on the basis of a few wavenumbers. 152 It was concluded that the FT-Raman spectra provided information on the degree of unsaturation as well as the relative proportions of SFA, MUFA and PUFA, with the intensities near 3013, 1663 and 1264 cm 1 in particular showing high correlation with the fatty acid profiles determined by gas chromatography.…”
Section: Fatmentioning
confidence: 99%
“…The main difficulties in the fats and oils analysis with classical dispersive Raman spectrometers are caused by the fluorescence due to sample impurities, specifically the carotenoid content (Levin and Lewis, 1990;Sadeghi-Jorabchi et al 1990). As the non-dispersive spectrometer seems better with regard to the analysis of fat and oils, only this instrument will be discussed here (Diem 1993;McCreery 2000).…”
mentioning
confidence: 99%
“…A sixth signal was observed above 3000 cm -1 due to stretching vibrations of the C-H bond of =C-H groups in fatty acid chains. According to Sadeghi-Jorabchi et al (1990), the signal shifts to higher wave numbers with increasing numbers of double bonds; thus, it appears at ca. 3006 cm -1 in oleate chains and ca.…”
Section: Raman Spectramentioning
confidence: 99%